2014
DOI: 10.3109/03630269.2014.963234
|View full text |Cite
|
Sign up to set email alerts
|

Blood Typing Profile of a School-Aged Population of a North Togo Township

Abstract: The aim of this study was the determination of hemoglobin (Hb) variants and ABO blood groups in a school population aged 6 to 9 years in the township of Agbandé-Yaka in North Togo. A cross-sectional study was carried out on 570 children of four primary schools at Agbande-Yaka, between March and July 2010. Hemoglobin characterization was done by alkaline buffer electrophoresis and the blood types ABO-Rhesus (Rh) D by immuno-hematological methods. A Hb variant was detected in 37.0% of the schoolchildren. Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As shown by Segbena et al (2005) in Togo there is an incidence at birth of 1.17% of the homozygous form SS and the national average is 1.3% and there is an increase of HbS/HbC at the northern part of the country (Vovor et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…As shown by Segbena et al (2005) in Togo there is an incidence at birth of 1.17% of the homozygous form SS and the national average is 1.3% and there is an increase of HbS/HbC at the northern part of the country (Vovor et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…There are more than 312,000 births of sickle cell children worldwide each year, with the vast majority of these births occurring in three countries: Nigeria, the Democratic Republic of Congo and India [4]. In Togo, a study was carried out by Vovor et al [5], on 570 children in the northern of the country and indicated a prevalence of 1.58% and 0%, respectively for Hb SC and Hb SS. Deaths caused by the complications of sickle cell disease are most often recorded in children under five, adolescents and pregnant women [6].…”
Section: Introductionmentioning
confidence: 99%